Tuberculosis Story - Mohit Gandhi (My University, 2021)
This is a story of Jeetan and Ram from Bihar, Vaishali district who migrate to Mumbai in search of work and start working at a construction site there in the stone crusher section. It highlights social and occupational risk factors of Tuberculosis and HIV and their interaction with the public health care delivery system. The case story highlights the journey of Jeetan and Ram from the development and manifestation of symptoms of TB to challenges in seeking treatment. The case study is divided into 9 sections, each section highlights some pertinent issues along with pointers for duscussion and some reflections.
Case Story
Keywords: Migrant Construction Workers with TB